Anthracocystis panici-leucophaei: A Potential Biological Control Agent for the Grassy Weed Digitaria insularis - Adriany Pena de Souza; Juliana Fonseca Alves; Eliane Mayumi Inokuti; Fernando Garcia; Bruno Wesley Ferreira; Thaisa Ferreira da Nobrega; Robert Weingart Barreto; Bruno Sérgio Vieira; Camila Costa Moreira (Agronomy)
Anthracocystis panici-leucophaei, causal agent of smut on Digitaria insularis (sourgrass), was evaluated as a biological control agent for this weed. Two types of inocula (teliospore and sporidia) were tested to assess its infectivity. The effects of teliospore and sporidia inoculations at different phenological stages of sourgrass were compared, as well as the potential of sporidia and teliospores in post-emergence sourgrass management. Virulence tests were conducted with the isolates obtained from D. insularis and evaluation of specificity of A. panici-leucophaei. Both teliospores and sporidia of A. panici-leucophaei are infective to D. insularis in three different phenological stages. Newly emerged plants with one pair of leaves are more sensitive to A. panici-leucophaei. Infection by A. panici-leucophaei inhibits the growth of sourgrass, decreasing several physiological parameters of D. insularis plants. The fungus produces systematic infection of sourgrass plants and may induce the formation of sori in a significant proportion of the plant panicles, partly castrating those plants. Among sixteen A. panici-peucophaei isolates tested, isolate 46 was the most virulent and inhibited the growth of sourgrass plants, and thus appears to have good potential as a biological control agent to be deployed against sourgrass. A. panici-leucophaei was demonstrated to be specific to D. insularis.